Naphthalene dianhydride based semifluorinated sulfonated copoly(ether imide)s: Synthesis, characterization and proton exchange properties - Mistri, Ershad Ali; Mohanty, Aruna Kumar; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte (Journal of Membrane Science, 2013)
A series of semifluorinated sulfonated copoly(ether imide)s (co-SPI) was synthesized by one pot high temperature polycondensation reaction using a sulfonated diamine, 4,4'-diaminostilbene-2,2'-disulfonic acid (DSDSA), 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA) and a fluorinated quadri diamine (QA). The structures of the resulting co-SPIs were investigated by FTIR and NMR spectroscopy. The polymers had high molecular weight and gave tough, flexible and transparent membranes. Oxidative stability of the membranes was improved by introducing trifluoromethyl substituents in the copolymer structure and the copolymers also exhibited superior mechanical property higher than many other SPIs. The co-SPI membrane showed significantly high proton conductivity and low activation energy in water medium. Microscopic analyses revealed that well-dispersed hydrophilic domains contribute to better proton conducting properties. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Activation energy; Fluorinated co-poly(ether imide)s; Proton conductivity; Transmission electron microscopy